2012
DOI: 10.4103/0973-8258.97102
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 fatty acids improve psychomotor performance via mechanism not related to nitric acid production

Abstract: Omega-3 fatty acids (ω-3FAs) are essential polyunsaturated fats that protect the brain from cognitive impairment. It increases the activity of endothelial nitric oxide synthetase (eNOS) and thereby increases the nitric acid (NO) production. This study aimed to explore the effect of ω-3FAs on psychomotor performance and to relate this effect to the reactive nitrogen species. This study was conducted in . Twenty healthy subjects, allocated randomly from medical college students, were participated in the single b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…Similar observation was reported by Hermer-Vaquez et al [15]; Al-Kuraishy et al [16]; Al-Kuraishy et al [17]. Animals fed on low protein diet usually stopped growing, lose weight, and sometimes adapt to the diet at a slow rate [18,19,20,21]. Our study agreed with this statement because cassava is low in protein and we observed weight drop in the rats fed with cassava only during our experiment.…”
Section: Discussionsupporting
confidence: 93%
“…Similar observation was reported by Hermer-Vaquez et al [15]; Al-Kuraishy et al [16]; Al-Kuraishy et al [17]. Animals fed on low protein diet usually stopped growing, lose weight, and sometimes adapt to the diet at a slow rate [18,19,20,21]. Our study agreed with this statement because cassava is low in protein and we observed weight drop in the rats fed with cassava only during our experiment.…”
Section: Discussionsupporting
confidence: 93%
“… 77 , 78 , 79 Remarkably, oxylipins derived from omega‐6 fatty acids are more proinflammatory than those derived from omega‐3 fatty acids and are involved in vasoconstriction and proliferation. 80 , 81 Omega‐3 fatty acids derived from oxylipins have antiinflammatory and vasodilatory effects. During inflammation higher expression of COX and LO‐5 trigger the production and release of oxylipins.…”
Section: Lipid Storm In Covid‐19mentioning
confidence: 99%
“…Oxylipins have anti‐inflammatory and/or proinflammatory effects in different diseases including fatty liver disease, atherosclerosis and Alzheimer's disease 77–79 . Remarkably, oxylipins derived from omega‐6 fatty acids are more proinflammatory than those derived from omega‐3 fatty acids and are involved in vasoconstriction and proliferation 80,81 . Omega‐3 fatty acids derived from oxylipins have antiinflammatory and vasodilatory effects.…”
Section: Lipid Storm In Covid‐19mentioning
confidence: 99%